2012
DOI: 10.1111/j.1467-7652.2011.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR156 in switchgrass (Panicum virgatum L.) results in various morphological alterations and leads to improved biomass production

Abstract: Switchgrass (Panicum virgatum L.) has been developed into a dedicated herbaceous bioenergy crop. Biomass yield is a major target trait for genetic improvement of switchgrass. microRNAs have emerged as a prominent class of gene regulatory factors that has the potential to improve complex traits such as biomass yield. A miR156b precursor was overexpressed in switchgrass. The effects of miR156 overexpression on SQUAMOSA PROMOTER BINDING PROTEIN LIKE (SPL) genes were revealed by microarray and quantitative RT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
281
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(298 citation statements)
references
References 54 publications
(118 reference statements)
10
281
1
2
Order By: Relevance
“…miR164 targets NAC transcription factor, and miR167 targets auxin response factors that play roles in plant signaling transduction and root development. It is interesting to note that those transcription factors are similar to those reported previously as miRNA targets for other plant species (Mallory et al, 2004;Arazi et al, 2005;Wu et al, 2006;Yang et al, 2006;Fu et al, 2012). In this study, we also found that scarecrow-like (SCL) protein 22 and mitochondrial transcription termination factor have near-perfect complementary sites with miR171 and miR426, respectively.…”
Section: Target Genes Of Mirnas and Their Expression Analysis Of Qrt-supporting
confidence: 70%
“…miR164 targets NAC transcription factor, and miR167 targets auxin response factors that play roles in plant signaling transduction and root development. It is interesting to note that those transcription factors are similar to those reported previously as miRNA targets for other plant species (Mallory et al, 2004;Arazi et al, 2005;Wu et al, 2006;Yang et al, 2006;Fu et al, 2012). In this study, we also found that scarecrow-like (SCL) protein 22 and mitochondrial transcription termination factor have near-perfect complementary sites with miR171 and miR426, respectively.…”
Section: Target Genes Of Mirnas and Their Expression Analysis Of Qrt-supporting
confidence: 70%
“…Field‐grown switchgrass transgenic lines with high sugar release or good growth phenotypes included those silencing or OE: (i) GAUT4, GAUT4 ‐knockdown (KD) lines down‐regulating expression of galacturonosyltransferase4 , a gene encoding an enzyme involved in pectin biosynthesis (Biswal et al ., Biswal, A.K., Atmodjo, M.A., Li, M., Yoo, C.G., Pu, Y., Lee, Y.‐C., Zhang, J.Y., Bray, A., King, Z., LaFayette, P., Mohanty, S.S., Ryno, D., Yee, K., Thompson, O.A., Rodriguez Jr, M., Winkeler, K., Collins, C., Yang, X., Tan, L., Sykes, R.W., Gjersing, E., Ziebell, A., Turner, G.B., Decker, S.R., Parrot, W., Udvardi, M.K., Mielenz, J., Davis, M.F., Nelson, R.S., Ragauskas, A.J., and Mohnen, D.); (ii) miRNA, miRNA156 ‐overexpression (OE) lines OE miRNA156, a regulator of plant developmental processes (Fu et al ., 2012); (iii) MYB4, MYB4 ‐OE lines OE PvMYB4, an R2R3‐type MYB repressor of the lignin biosynthetic pathway (Shen et al ., 2012, 2013); (iv) COMT, COMT ‐KD lines down‐regulating expression of caffeic acid O ‐methyltransferase, a lignin biosynthetic gene (Fu et al ., 2011); and (v) FPGS, FPGS ‐KD lines down‐regulating expression of folylpolyglutamate synthase 1 , a gene encoding a C1 metabolism enzyme believed to provide methyl groups for lignin biosynthesis (Srivastava et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Conventional and transgenic approaches have been utilized to generate switchgrasses with improved quality, based primarily on the reduction of lignin content as a means to improve ethanol yields through fermentation of biomass [73,[122][123][124][125], and possibly for increased yields or plant development using transgenic routes [126,127]. The application of biotechnology for switchgrass improvement has been reviewed recently [17].…”
Section: Switchgrass As a Temperate C 4 Warm-season Grass Modelmentioning
confidence: 99%